Detecting high-risk chronic kidney disease–mineral bone disorder phenotypes among patients on dialysis: a historical cohort study. Issue 4 (27th August 2018) - Neri, Luca; Kreuzberg, Ursula; Bellocchio, Francesco; Brancaccio, Diego; Barbieri, Carlo; Canaud, Bernard; Stuard, Stefano; Ketteler, Markus
Abstract: Background: The clinical management of chronic kidney disease–mineral bone disorder (CKD-MBD) remains extremely challenging, partially due to difficulties in defining high-risk phenotypes based on serum biomarkers. We evaluated the prevalence and outcomes of 27 mutually exclusive CKD-MBD phenotypes in a large, multi-national cohort of chronic dialysis patients over a 5-year follow-up study. Methods: In this historical cohort study, we enrolled all haemodialysis patients registered in EuCliD ® on 1 July 2011 across 28 Europe, the Middle East and Africa (EMEA) and South American countries. We created 27 mutually exclusive phenotypes based on combinations of serum parathyroid hormone (PTH), phosphorus (P) and calcium (Ca) 6-month averages (L, low; T, target; H, high). We tested the association between CKD-MBD phenotypes and 5-year mortality and hospitalization risk by outcome risk score-adjusted proportional hazard regression. Results: We enrolled 35 721 eligible patients. Eastern European and South American countries generally achieved poorer CKD-MBD control when compared with Western European countries (prevalence ratio: 0.79; P < 0.001). There were 15 795 deaths [126.7 deaths/1000 person-years; 95% confidence interval (CI) 124.7–128.7]; 18 014 had at least one hospitalization (203.9 hospitalizations/1000 person-years; 95% CI 201.0–206.9); the incidence of the composite endpoint was 280.0 events/1000 person-years (95% CI 276.6–283.5). In the fully adjusted model, relative mortality risk ranged from hazard ratio (HR) = 1.07 (PTH/Ca/P: TLT) to HR = 1.59 (PTH/Ca/P: LTL), whereas the relative composite endpoint risk ranged from HR = 1.07 (PTH/Ca/P: TTH) to HR = 1.36 (PTH/Ca/P: LTL). Conclusion: We identified several CKD-MBD phenotypes associated with reduced hospitalization-free survival and increased mortality. Ranking of relative risk estimates or excess events concurs in informing healthcare priority setting.